The effective control using biopesticide insects glue against the main pest Empoasca on tea plant - Odih Sucherman (Jurnal Penelitian Teh dan Kina, 2011)
The observation of theÂ  control of bio-diversity the main pest Empoasca on tea plantation effective, efficient and neighborly environment has been undertaken testing insects glue as biodiversity control to main pests Empoasca in the field. The research done in the Pasir Sarongge Experimental Garden (1.100 m asl), Cianjur, West Java. Testing designed in random block design (RBD) with 5 treatment and 5 replication. Treatment tested were: (1) formulation of glue M-5; (2) formulation of glue M-10; (3) formuÂlation of glue M-15; (4) formulation of glue comparator; (5) untreated. All the treatment of glue was applied by means of smeared on mineral water bottle (600 ml), every plot installed 5 bottle. Parameters in the observations were the population Empoasca trapped in glue, and intensity attack Empoasca. Research results in a laboratory pointed out that glue M-5 more effectively entraps pests Empoasca when compared to another formuÂlation, and comparator glua, as well untreated. Whereas the results of observation in the overall pointed out that the use of formulation of glue M-5 which is formulation lowest have enough effectively to catch pests Empoasca in the field was 19,83 head trap or the equivalent to the 79,32 head any every plot in the area plot 50 m2. The arrest shall taller when experiments was undertaken in dry season.